HUBUNGAN SPIRITUALITAS DAN MOTIVASI KERJA DENGAN KINERJA GURU PENDIDIKAN AGAMA KRISTEN DI KECAMATAN TARUTUNG DAN ADIANKOTING KABUPATEN TAPANULI UTARA TAHUN 2017 - laia, fanorotodo (IAKN Tarutung, 2019)
v Abstract, This research aims to know the relationship of spirituality and motivation of working together WithChristian education teacher Performance in Tarutung of North Tapanuli Regency and Adiankoting the year2017. This research uses descriptive quantitative methods approach. The population of the research was thewhole Christian religious education teachers in district of Tarutung and Adiankoting that add up to 31 peoplewith samples of 31 people. Research instrument in the form of the now closed, compiled by researchers basedon variable indicator research. Testing now done to 30 respondents who are not research samples, and havebeen tested with test validity and reliability.The third hypothesis in this study received the truth with data: 1) Correlation coefficient and 0.584 X1Y ofdetermination of 34.10%. This suggests that the performance guru 34.10% determined by the teachers ofspirituality. 2) Correlation of X2Y 0.631 and coefficient of determination of 39.81%. This suggests that theperformance guru 39.81% determined by the motivation to work. 3.) Double RX1X2Y = 0.664 Correlation andcoefficient of determination R2 = double 44.08%, which means the performance of teachers of 44.08%determined by the spirituality and motivation of working together, partly ditentukani by other factors as onproblem identification.Based on the results of the research can be concluded there is a positive relationship between spiritualityand motivation of working with Christian religious education teacher performance in Tarutung of NorthTapanuli Regency and Adiankoting the year 2017 in singly or together because it has been tested empirically.The implication, if will improve performance, teachers should increase spirituality and motivation of work.Keywords : spirituality, work motivation, performance